Estudio del efecto de dispositivos de control de flujo activo en la eficiencia aerodinámica de una turbina eólica de eje horizontal. (2023)
The present study was based on the analysis of the DU17DBD25 aerodynamic profile used in wind turbine blades. Simulations were carried out in the ANSYS Fluent program, varying the inclination angles of the wing profile between -20 and 20° and evaluating the drag and lift coefficients. Flow control devices called synthetic jets were implemented. The analyzes were carried out with jet and without synthetic jet. These results were compared with those obtained through the Blade Element Momentum Theory. The results of the simulations without synthetic jet were validated with respect to the values ​​found in the literature, tending to behave similarly. A 10% improvement in the lift coefficient and a delay in the higher flow separation angle was obtained for angles of attack greater than 15°, which shows the increase in the performance of the wind turbine.